Le corporatisme fasciste à l’étranger : circulations, réceptions, hybridations - Claire Lorenzelli; Matteo Pasetti (Laboratoire Italien)
This special issue delves into the circulation, reception, and forms of hybridisation of Fascist Italy’s corporatism around the world between the 1920s and the 1950s. By postulating the idea of an Italian and international “corporative laboratory”, this issue aims at offering a transnational history of this political, economic, and social model.